Influence of colour changes and moisture content during banana drying on laser backscattering - Romano, Giuseppe; Argyropoulos, Dimitrios; Gottschalk, Klaus; Cerruto, Emanuele; Muller, Joachim (International Journal of Agricultural and Biological Engineering, 2010)
Pre-drying treatments are frequently employed to preserve fruit quality. The objective of this research was to monitor colour changes of banana during drying by laser backscattering and to determine the influence of the fruit discolouration on the light distribution into banana tissue. Moreover, to examine the influence of drying on the laser backscatter, the relationship between moisture content and relative laser area of banana slices was analyzed with different degrees of colour degradation. The experiments were conducted at drying air temperature of 63